Surgical Treatment of Atrial Fibrillation: A Review - Nadine Hiari (Cardiology Research and Practice)
Atrial fibrillation is the most commonly sustained arrhythmia in man. While it affects millions of patients worldwide, its incidence will markedly increase with an aging population. Primary goals of AF therapy are to (1) reduce embolic complications, particularly stroke, (2) alleviate symptoms, and (3) prevent long-term heart remodelling. These have been proven to be a challenge as there are major limitations in our knowledge of the pathological and electrophysiological mechanisms underlying AF. Although advances continue to be made in the medical management of this condition, pharmacotherapy is often unsuccessful. Because of the high recurrence rate of AF despite antiarrhythmic drug therapy for maintenance of sinus rhythm and the adverse effects of these drugs, there has been growing interest in nonpharmacological strategies. Surgery for treatment of AF has been around for some time. The Cox-Maze procedure is the gold standard for the surgical treatment of atrial fibrillation and has more than 90% success in eliminating atrial fibrillation. Although the cut and sew maze is very effective, it has been superseded by newer operations that rely on alternate energy sources to create lines of conduction block. In addition, the evolution of improved ablation technology and instrumentation has facilitated the development of minimally invasive approaches. In this paper, the rationale for surgical ablation for atrial fibrillation and the different surgical techniques that were developed will be explored. In addition, it will detail the new approaches to surgical ablation of atrial fibrillation that employ alternate energy sources.